INFANT MORTALITY IN THE MUNICIPALITY OF RIO VERDE - Leão, Aline Gonçalves; Oliveira, Ana Carolina Donda; Parreira, Gislaine Leão; Furquim, Késsio Guerreiro; Junqueira, Marina Porto Ferreira; Ferreira, Rogerio Alves; da Silva, Vanessa Cervi (Seven Editora, 2024)
Infant mortality is widely recognized as an essential indicator of quality of life and health services in a population. This study was carried out in the municipality of Rio Verde, Goiás, between 2019 and 2023, with the objective of identifying patterns and determinants of infant mortality, in addition to evaluating the effectiveness of local health policies. The descriptive methodology was based on data from the SIM and SINASC systems, analyzing live births and infant deaths, focusing on characteristics such as birth weight, gestational age, causes of death, place of care and socioeconomic profile of the mothers. The results revealed that, over the five years analyzed, there was a gradual reduction in infant mortality, with emphasis on a significant drop between 2021 and 2022, the main causes of death were perinatal complications, neonatal infections, and low birth weight, prevailing among neonates with a gestational age below 37 weeks. A higher mortality rate was also observed among male children, a fact that follows the national trend. The conclusion reinforces the need to strengthen prenatal care, improve the infrastructure of health facilities and train professionals, especially those involved in neonatal care. Interventions aimed at promoting maternal and child health, such as awareness campaigns on the importance of prenatal care, breastfeeding and immunization, are recommended. Improving the quality of death records and continuous surveillance of these data are crucial to guide more effective public policies aimed at the sustainable reduction of infant mortality rates in Rio Verde. DOI:https://doi.org/10.56238/sevened2024.029-048